1986
DOI: 10.1093/nar/14.13.5417
|View full text |Cite
|
Sign up to set email alerts
|

The nucleotide sequence of tobacco vein mottling virus RNA

Abstract: The nucleotide sequence of the RNA of tobacco vein mottling virus, a member of the potyvirus group, was determined. The RNA was found to be 9471 residues in length, excluding a 3'-terminal poly(A) tail. The first three AUG codons from the 5'-terminus were followed by in-frame termination codons. The fourth, at position 206, was the beginning of an open reading frame of 9015 residues which could encode a polyprotein of 340 kDa. No other long open reading frames were present in the sequence or its complement. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
172
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(183 citation statements)
references
References 40 publications
10
172
1
Order By: Relevance
“…The flexuous particles contain a single-stranded messenger RNA of about 10000 nucleotides with a viral protein covalently linked to the 5' end and a poly(A) tail at the 3' end (for a review see Riechmann et al, 1992). The complete nucleotide sequence of several members of the group is already known (Allison et al, 1986;Domier et al, 1986;Robaglia et al, 1989;Lain et al, 1989;Maiss et al, 1989;Teycheney et al, 1989;Johansen et al, 1991 ; * Author for correspondence. Fax +33 1 30 83 31 95. e-mail robaglia@oxygene.versailles.inra.fr Nicolas & Lalibertr, 1992;Yeh et al, 1992;Jayaram et al, 1992;Vance et al, 1992;Thole et al, 1993;Palkovics et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The flexuous particles contain a single-stranded messenger RNA of about 10000 nucleotides with a viral protein covalently linked to the 5' end and a poly(A) tail at the 3' end (for a review see Riechmann et al, 1992). The complete nucleotide sequence of several members of the group is already known (Allison et al, 1986;Domier et al, 1986;Robaglia et al, 1989;Lain et al, 1989;Maiss et al, 1989;Teycheney et al, 1989;Johansen et al, 1991 ; * Author for correspondence. Fax +33 1 30 83 31 95. e-mail robaglia@oxygene.versailles.inra.fr Nicolas & Lalibertr, 1992;Yeh et al, 1992;Jayaram et al, 1992;Vance et al, 1992;Thole et al, 1993;Palkovics et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The complete nucleotide sequence of seven different potyviruses has been documented: tobacco etch virus (TEV) (Allison et al, 1986), tobacco vein mottling virus (TVMV) (Domier et al, 1986), plum pox virus (PPV) (Maiss et al, 1989;La~n et al, 1989), the necrotic strain of potato virus Y (PVY N) (Robaglia et al, 1989), pepper mottle virus (PepMoV) (Vance et al, 1992), turnip mosaic potyvirus (TuMV) (Nicolas & Lalibert& 1992) and pea seed-borne mosaic virus (Johansen et al, 1991). The sequence analysis of potyviruses and in vitro translation studies of potyvirus genomic RNAs have revealed a single open reading frame (ORF) encoding a large polyprotein.…”
mentioning
confidence: 99%
“…Hybrids were treated with 2 units of RNase H at 37 °C for 1 h, denatured with formamide and formaldehyde and analysed by electrophoresis in 1 ~o agarose gels containing formaldehyde. When the RNA was annealed to the oligonucleotide complementary to a region near the 3' terminus of the RNA (Domier et al, 1986) and then treated with RNase H, the aggregates were not eliminated (Fig. 2b, lane 3).…”
mentioning
confidence: 99%